The role and importance of management in modern sports - Chyhrinova, S.; Poliakova, Oksana (Національний технічний університет "Харківський політехнічний інститут", 2025)
In advanced sports, where each day brings unused challenges, a great supervisor is exceptionally vital. Sports administration isn't fair a buzzword - it may be a genuine device that helps groups and clubs not as it were survive, but develop within the quick world of competition and commerce. Envision a sports club as a transport in a huge storm. Without a good captain, even the most excellent team can lose its way. Great administration is just like the wheel of the dispatch – it makes a difference the group direct within the right course when there are numerous changes and solid competition. Nowadays, sports directors face many challenges. The world is exceptionally associated presently, and computerized innovation is changing the rules exceptionally rapidly. So it is exceptionally critical to alter rapidly and bring modern thoughts.
Keywords: sports management; leadership; team operations; marketing strategy; financial planning; talent development; modern sports